Atomic Force Microscope with an Adjustable Probe Direction and Integrated Sensing and Actuation - Schaude, Janik; Hausotte, Tino (Nanomanufacturing and Metrology, 2022)
This article presents the application and evaluation of a cantilever with integrated sensing and actuation as part of an atomic force microscope (AFM) with an adjustable probe direction, which is integrated into a nano measuring machine (NMM-1). The AFM, which is operated in closed-loop intermittent contact mode, is based on two rotational axes that enable the adjustment of the probe direction to cover a complete hemisphere. The axes greatly enlarge the metrology frame of the measuring system by materials with a comparatively high coefficient of thermal expansion, which ultimately limits the achievable measurement uncertainty of the measuring system. Thus, to reduce the thermal sensitivity of the system, the redesign of the rotational kinematics is mandatory. However, in this article, some preliminary investigations on the application of a self-sensing cantilever with an integrated micro heater for its stimulation will be presented. In previous investigations, a piezoelectric actuator has been applied to stimulate the cantilever. However, the removal of the piezoelectric actuator, which is enabled by the application of a cantilever with an integrated micro heater, promises an essential simplification of the sensor holder. Thus, in the future it might be possible to use materials with a low coefficient of thermal expansion, which are often difficult to machine and therefore only allow for rather simple geometries. Furthermore, because of the creepage of piezoelectric actuators, their removal from the metrology frame might lead to improved metrological characteristics. As will be shown, there are no significant differences between the two modes of actuation. Therefore, the redesigned rotational system will be based on the cantilever with integrated sensing and actuatio
Keywords: Atomic force microscopy; Tilting AFM; Piezoresistive cantilever; Self-actuated cantilever; Nano measuring machine

Atomic force microscope with an adjustable probe direction and piezoresistive cantilevers operated in tapping-mode - Schaude, Janik; Albrecht, Julius; Klöpzig, Ute; Gröschl, Andreas Christian; Hausotte, Tino (Technisches Messen, 2019)
This article presents a new tilting atomic forcemicroscope (AFM) with an adjustable probe direction and piezoresistive cantilever operated in tapping-mode.The AFM is based on two rotational axes, which enable the adjustment of the probe direction to cover a complete hemisphere. The whole setup is integrated into a nano measuring machine (NMM-1) and the metrological traceability of the piezoresistive cantilever is warranted by in situ calibration on the NMM-1. To demonstrate the capabilities of the tilting AFM, measurements were conducted on a step height standar
Keywords: Atomic force microscopy; tilting AFM; piezoresistive cantilever; nano measuring machine

Bidirectional confocal measurement of a microsphere - Schaude, Janik; Baumgärtner, Benjamin; Hausotte, Tino (Applied Optics, 2021)
This paper presents the bidirectional confocal measurement of a microsphere, which enables the simple measurement of the sphere with a similar number of measuring points taken on its upper and its lower hemispheres. The innovative measuring strategy is the placement of the sphere above a mirror and the subsequent measurement of the upper hemisphere on the real sphere and the lower hemisphere on the mirrored sphere. While theoretical explanations are given first, the main focus of the paper is the presentation of the idea itself and the very promising empirical findings. We believe these findings prove that the measuring strategy presented has the potential to become a prime method for the optical characterization of microsphere

Effect of a Misidentified Centre of a Type ASG Material Measure on the Determined Topographic Spatial Resolution of an Optical Point Sensor - Schaude, Janik; Gröschl, Andreas Christian; Hausotte, Tino (Metrology, 2022)
The article presents the determination of the topographic spatial resolution of an optical point sensor. It is quantified by the lateral period limit DLIM measured on a type ASG material measure, also called (topographic) Siemens star, with a confocal sensor following both a radial measurement and evaluation, as proposed by ISO 25178-70, and the measurement and subsequent evaluation of two line scans, proposed by the NPL Good Practice Guide. As will be shown, for the latter, an only slightly misidentified target centre of the Siemens star leads to quite significant errors of the determined DLIM. Remarkably, a misidentified target centre does not necessarily result in an overestimation of DLIM, but lower values might also be obtained. Therefore, a modified Good Practice Guide is proposed to determine DLIM more accurately, as it includes a thorough determination of the centre of the Siemens star as well. While the measurement and evaluation effort is increased slightly compared to the NPL Good Practice Guide, it is still much faster than a complete radial measurement and evaluation.
Keywords: surface metrology; topographic spatial resolution; lateral period limit; type ASG material measure; Siemens star; confocal sensor; nano measuring machine

Evaluation of the optical performance of a novel high-speed focal-distance-modulated fibre-coupled confocal sensor - Gröschl, Andreas Christian; Schaude, Janik; Hausotte, Tino (Proceedings of SPIE - The International Society for Optical Engineering, 2019)
This article presents the evaluation of the optical performance of a new high-frequency focal-distance-modulated confocal point sensor. While maintaining the known advantages of the confocal measurement principle, the sen- sor represents an innovative combination of a fibre-coupled confocal illumination and detection with a tuneable, acoustically driven gradient-index fluid lens (TAG lens) for the modulation of the focus distance and a novel signal processing utilizing a lock-in amplifier. The new arrangement is able to achieve an approximately linear characteristic curve for the optimised feedback control of nano coordinate measuring systems (CMS) in scanning sample mode. This article emphasises the implementation and use of the sensor in nano CMS (NMM-1) and the advantages of the new signal processing. Measurements on different resolution standards are conducted and compared with the focal-distance-modulated sensor and without focus-distance-modulation as conventional confocal microscope (CCM).
CRIS-Team Scopus Importer:2019-12-31
Keywords: Confocal microscopy; Nano coordinate measuring system; Surface measurement

Evaluation und Justierung eines neuartigen, hochfrequent fokusabstandsmodulierten, fasergekoppelten, konfokalen Punktsensors für axial geregelte Oberflächenmessungen mit einem Nanokoordinatenmessgerät - Gröschl, Andreas Christian; Schaude, Janik; Hausotte, Tino (Technisches Messen, 2019)
This article presents measurements of surfaces by performing closed-loop line scans using a nano coordinate measuring system (NMM-1) [T. Hausotte, B. Percle, and G. Jager. Meas. Sci. Technol., 2009] and a new highfrequency focal-distance-modulated confocal point sensor. While maintaining the known advantages of the confocal measurement, the sensor represents an innovative combination of a fibre-coupled confocal illumination and detection with a tuneable, acoustically driven gradientindex fluid lens (TAG-lens) [Tag Optics Inc. Datasheet, 2013] for modulation of the focus distance and a novel signal processing utilizing a lock-in amplifier. The new arrangement is able to achieve an approximately linear characteristic curve for the optimised feedback control of a coordinate measuring system (CMS) in scanning sample mode. This article emphasises the implementation and use of the sensor in a coordinate measuring system and the advantages of lateral closed-loop scans holding the distance between the sample and the objective constant compared to conventional lateral scans in axial stepwise layers. The enormous saving of time eventuates in measurements with reduced measurement errors due to less thermal drifts.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Confocal sensor; nano coordinate measuring machine; surface measurement

Evaluation und Korrektur thermischer Driften eines hochfrequent fokusabstandsmodulierten, fasergekoppelten konfokalen Punktsensors - Gröschl, Andreas Christian; Schaude, Janik; Hausotte, Tino (Technisches Messen, 2019)
In diesem Artikel wird die Messpräzision eines hochfrequent fokusabstandsmodulierten, fasergekoppelten Konfokalsensors unter temperaturstabilen Bedingungen bestimmt. Insbesondere in der Mikro- und Nanomesstechnik verursachen thermische Driften signifikante Messabweichungen. Diese lassen sich bei wiederholten Messungen zwar zu einem großen Teil korrigieren, innerhalb einer Messung ist dies bisher jedoch nicht möglich. Das verwendete Nanokoordinatenmesssystem (NMM-1) wurde daher um eine Temperierhaube erweitert, um thermische Driften zu minimieren. Weiterhin wird die Temperatur mittels kalibrierter Pt100-Temperatursensoren während der Messungen erfasst, um die Korrelation des Messergebnisses und der Temperatur quantitativ zu bestimmen. Inwiefern die Korrektur des Messergebnisses anhand der aufgenommenen Temperatur möglich ist, wird in diesem Artikel evaluier
Keywords: Konfokalsensor; Nanokoordinatenmessgerät; Temperaturkompensation

High-speed focal-distance-modulated fiber-coupled confocal sensor for coordinate measuring systems - Hausotte, Tino; Gröschl, Andreas Christian; Schaude, Janik (Applied Optics, 2018)
This article presents a new robust, precise, high-frequency focal-distance-modulated confocal point sensor for probing in coordinate measuring systems (CMSs). While maintaining the known advantages of the confocal measurement principle, the sensor represents an innovative combination of a fiber-coupled confocal illumination and detection with a tuneable, acoustically driven gradient-index fluid lens for modulation of the focus distance and a novel signal processing utilizing a lock-in amplifier. The new arrangement is able to achieve an approximately linear characteristic curve for the optimized feedback control of the CMS in scanning sample mode. This article emphasizes the optical application and the signal processing of the setu

Improvements of a high-speed focus distance modulated fibrecoupled confocal sensor for nanocoordinate measuring systems - Gröschl, Andreas Christian; Köhnen, Stephan; Schaude, Janik; Hausotte, Tino (SENSOREN UND MESSSYSTEME 19. ITG/GMA-Fachtagung, 2018)
This article presents improvements of a new robust, precise, high-frequency focal-distance-modulated confocal point sensor for probing in coordinate measuring systems (CMS). While maintaining the known advantages of the confocal measurement principle, the sensor represents an innovative combination of a ﬁbre-coupled confocal illumination and detection with a tuneable, acoustically driven gradient-index ﬂuid lens (TAG lens) for modulation of the focus distance andanovelsignalprocessingutilizingalock-inampliﬁer. Thenewarrangementisabletoachieveanapproximatelylinear characteristiccurvefortheoptimisedfeedbackcontroloftheCMSinscanningsamplemode. Thisarticleemphasisesthe improvement of the lock-in ampliﬁcation by using a custom signal processing on the basis of a ﬁeld programmable gate array (FPGA).<br

Investigations on the accuracy and evaluation of the uncertainty of stitching in optical surface metrology - Schaude, Janik; Hausotte, Tino (Optical Measurement Systems for Industrial Inspection XIII, 2023)
Exemplified by a stitching procedure that is frequently applied in optical surface metrology and that is based on the maximization of the cross-correlation function, the article shows the dependency of the accuracy of a stitching result on many different interdependent influence factors. Furthermore it is shown that the remaining deviations of the regions that are regarded to be the overlapping ones is no generally valid indication for the accuracy of a stitching result. Thus, in the second part of the article, a method to determine the uncertainty of a stitching result based on a Monte Carlo simulation is presented. The input quantities of the stitching procedure, namely the topographic data of the sub-apertures and the position and orientation data of the positioning system are characterized by a probability density function. Afterwards, it is sampled randomly from these probability density functions and the stitching procedure is applied many times. From the obtained distributions, the result of the stitching procedure along with its uncertainty is derived. The obtained results show metrological compatibility to the true values and furthermore enable the recognition of the cases for which the stitching did not improve but impair the accuracy compared to the accuracy of the positioning system. <br

Investigations on the measurement precision of an atomic force microscope with an adjustable probe direction - Schaude, Janik; Hausotte, Tino (euspen's 21st International Conference & Exhibition, 2021)
The article presents measurements with an atomic force microscope (AFM) with an adjustable probe direction integrated into a nano measuring machine (NMM-1). The AFM, consisting of a commercial piezoresistive cantilever operated in closed-loop intermitted contact-mode, is based on two rotational axes, which enable the adjustment of the probe direction to cover a complete hemisphere. The axes greatly enlarge the metrology frame of the measuring system by materials with a comparatively high coefficient of thermal expansion. Therefore, the long-term measurement precision of the setup and its sensitivity to thermal variations is investigated within a thermostating housing with a long-term temperature stability of 17 mK. On the other hand, the thermostating housing necessitates long signal paths, as the signal processing units are located outside of it. Therefore, the short-term measurement precision is determined by repeated calibrations of the AFM against the traceable z-interferometer of the NMM-1 and the z-noise is determined by standstill measurements. Furthermore, the tilting-capacity of the AFM is applied for repeated measurements of a calibration grating with a nominal step height of (21.4 ±1.5) nm. It is measured while placed within the xy-plane of the NMM-1 and while tilted to this plane with the probe direction adjusted accordingly. The determined mean step heights for both positions of the grating with 21.42 nm and 21.18 nm and standard deviations in the double-digit pm-range agree well with the nominal step height. Furthermore, the noise-level and the short-term measurement precision are in the low single-digit nm-range. Nevertheless, the empirically determined thermal sensitivity of the sensor is about 1.3 nm/mK.<br
Keywords: Atomic force microscopy; tilting-AFM; piezoresistive cantilever; nano measuring machine

Kontinuierliche laterale Abtastung von Oberflächen durch axiale Regelung des Arbeitsabstandes in einem Nanokoordinatenmessgerät mit einem hochfrequent fokusabstandsmodulierten, fasergekoppelten, konfokalen Punktsensor - Gröschl, Andreas Christian; Schaude, Janik; Hausotte, Tino (Technisches Messen, 2018)
In diesem Artikel wird ein neues Messverfahren zur Oberflächenmessung bei gleichzeitiger axialer Regelung des Arbeitsabstandes eines hochfrequent fokusabstandsmodulierten, fasergekoppelten, konfokalen Punktsensors in einem Nanokoordinatenmessgerät (NMM-1) vorgestellt. Während bei diesem Verfahren alle bekannten Vorteile der Konfokaltechnik beibehalten werden, stellt die innovative Kombination einer fasergekoppelten Beleuchtung und Detektion mit einer akustisch getriebenen, modulierbaren Flüssigkeitsgradientenlinse (engl. tunable, acoustically driven gradient-index fluid lens, Abk. TAG-Linse) zur hochfrequenten Abstandmodulation des Fokus zusammen mit einer neuartigen Signalverarbeitung auf Basis einer Lock-in-Verstärkung eine wesentliche Verbesserung dar. Durch die Anordnung und Auswertung ergibt sich im Gegensatz zu konventionellen konfokalen Punktsensoren eine nahezu lineare Kennlinie, wobei die Richtung der Abweichung der Messobjektoberfläche relativ zur Fokusebene des Objektivs eindeutig bestimmt werden kann. Es wird insbesondere die Verwendung des Sensors sowie die Nutzung der resultierenden Kennlinie zur Regelung der Oberflächenposition in einem Nanokoordinatenmessgerät gezeigt. Im Gegensatz zum Verfahren konventioneller Konfokalsensoren, bei der lateral flächenhafte Abtastungen auf vielen diskreten axialen Höhen durchgeführt werden, um daraus für jeden lateralen Messpunkt durch eine Maximalwertsuche einen Höhenwert zu ermitteln, kann durch die gezeigte Nachregelung eine Oberflächenerfassung durch eine einzige laterale Abstastung erfolgen. Die sich daraus ergebende immense Zeitersparnis ist nicht nur wesentlich ökonomischer sondern weist aufgrund zeitlicher thermischer Driften auch geringere Messabweichungen auf.
CRIS-Team WoS Importer:2019-04-12
Keywords: Konfokalsensor; Nanokoordinatenmessgerät; Oberflächenmessung

Large range closed-loop scans with a focal-distance-modulated confocal sensor - Schaude, Janik; Gröschl, Andreas Christian; Hausotte, Tino (Procedia CIRP, 2020)

Lightweight Control Method for Dielectric Elastomer Actuators as Self-Sensing Artificial Muscles - Landgraf, Maximilian; Ollech, Johannes; Klemm, Tobias; Schaude, Janik; Reitelshöfer, Sebastian; Franke, Jörg (2nd IEEE International Conference on Cyborg and Bionic Systems (CBS), 2018)

Redesigned Sensor Holder for an Atomic Force Microscope with an Adjustable Probe Direction - Schaude, Janik; Fimushkin, Maxim; Hausotte, Tino (International Journal of Precision Engineering and Manufacturing, 2021)
The article presents a redesigned sensor holder for an atomic force microscope (AFM) with an adjustable probe direction, which is integrated into a nano measuring machine (NMM-1). The AFM, consisting of a commercial piezoresistive cantilever operated in closed-loop intermitted contact-mode, is based on two rotational axes, which enable the adjustment of the probe direction to cover a complete hemisphere. The axes greatly enlarge the metrology frame of the measuring system by materials with a comparatively high coefficient of thermal expansion. The AFM is therefore operated within a thermostating housing with a long-term temperature stability of 17 mK. The sensor holder, connecting the rotational axes and the cantilever, inserted one adhesive bond, a soldered connection and a geometrically undefined clamping into the metrology circle, which might also be a source of measurement error. It has therefore been redesigned to a clamped senor holder, which is presented, evaluated and compared to the previous glued sensor holder within this paper. As will be shown, there are no significant differences between the two sensor holders. This leads to the conclusion, that the three aforementioned connections do not deteriorate the measurement precision, significantly. As only a minor portion of the positioning range of the piezoelectric actuator is needed to stimulate the cantilever near its resonance frequency, a high-speed closed-loop control that keeps the cantilever within its operating range using this piezoelectric actuator further on as actuator was implemented and is presented within this article.<br
Keywords: Atomic force microscopy; Tilting-AFM; Piezoresistive cantilever; Nano measuring machine

Stitched open-loop measurements with a focal-distance-modulated confocal sensor - Schaude, Janik; Gröschl, Andreas Christian; Hausotte, Tino (Technisches Messen, 2021)
The article presents measurements with a high-speed focal-distance modulated fibre-coupled confocal sensor integrated into a nano measuring machine (NMM-1). Combined with an appropriate signal processing, this axial beam modulating sensor yields a linear characteristic curve within a range of about 600 nm. This characteristic curve enables scans in closed-loop constant distance mode, where the controller of the NMM-1 keeps the distance between the measured surface and the sensor constant. Therefore, only one lateral scan is necessary to measure a given topography. Nevertheless, it is also possible to conduct open-loop constant height measurements on discrete heights. The axial offset between the heights needs to be only slightly less than the measuring range of the sensor, leading to a great reduction of the number of needed lateral scans to measure a given topography compared to a conventional confocal sensor, where the axial offset for a similar optical system is typically about 50 nm. To combine the scans taken at different heights, it is possible to stitch them using overlapping measuring points taken at two adjacent heights. Within this article, measurements are conducted on a roughness standard in closed-loop constant distance and in open-loop constant height mode, where the latter are evaluated with and without the application of the stitching algorith
Keywords: Confocal sensor; roughness measurement; focal-distance-modulation; stitching; nano measuring machine

Uncertainty-based determination of recalibration dates - Schaude, Janik; Hausotte, Tino (International Journal of Metrology and Quality of Engineering, 2024)
Traceability is of vital importance in metrology and is achieved by an unbroken chain of calibrations that relate the measurement result to a reference. Less clear is the temporal aspect of traceability, namely the determination of recalibration dates. Relevant standards require the conduction of recalibrations in a planned manner, and thus in general there is a calibration history consisting of a number of past calibrations for measurands that are part of the traceability chain. Nevertheless, commonly only the results of the last calibration of the standards of the traceability chain are considered when determining a measurement result. Furthermore, recalibration dates are often determined in a rather unscientific manner. Within this paper, a method is proposed to predict the current value of a measurand along with its uncertainty, taking into account all past calibrations. Based on the predetermined target measurement uncertainty of the measurand, it is possible to recognize the need for and thus to date recalibrations. The applicability of the method is investigated by examining the metrological compatibility of the predicted results with the results of subsequent calibrations of the calibration histories of a number of different standards. There is an explainable limitation of the applicability of the method to calibration histories that exhibit a correlation of time and the chosen calibration laboratory. However, the paper leads the way of future research to remedy the currently unsatisfying state regarding the handling of calibration histories and the determination of recalibration dates.<br
Keywords: calibration; calibration interval; measurement uncertainty; traceability